Who Deserves To Be Supported? Analysing Attitudes Towards Horizontal Redistribution in Nigeria - Langer, Arnim (2024)
Despite the widespread recognition of the risk that group‐based inequalities, or so‐called horizontal inequalities (HIs), pose for the political stability and social cohesion of multi‐ethnic societies, extremely little research has been conducted on how people perceive these inequalities and how these perceptions, in turn, are associated with people’s attitudes towards group‐based or horizontal redistribution. In this article, we systematically analyse how people’s perceptions of prevailing socio‐economic HIs shape their attitudes towards horizontal redistribution in Nigeria, a country confronted with sharp and persistent inequalities between different ethnic groups. We develop a set of hypotheses for explaining differences in support for horizontal redistribution policies and test these hypotheses empirically with the help of a unique survey panel of about 2300 Nigerians.